OPTIMIZING RECRUITMENT STRATEGIES: AN AHP APPROACH TO EVALUATING HIRING CRITERIA AND METHODS (International Journal of Food and Nutritional Sciences, 2023)
This study utilizes the Analytic Hierarchy Process (AHP) to optimize recruitment strategies by evaluating and selecting the most effective hiring criteria and methods. The goal is to enhance the quality of new hires and streamline the recruitment process. The research identifies five critical attributes—Cost-Effectiveness, Time Efficiency, Candidate Quality, Candidate Experience, and Fit with Organizational Needs—and assesses three recruitment alternatives: Online Job Portals, Recruitment Agencies, and Employee Referral Programs. The AHP analysis reveals that Candidate Experience and Candidate Quality are the most important attributes, with Recruitment Agencies emerging as the most effective recruitment method. The consistency ratio analysis confirms the reliability of the results. The study provides actionable insights for organizations to improve their recruitment strategies by focusing on candidate-centric factors and leveraging effective methods. This approach not only enhances recruitment outcomes but also aligns with organizational needs, leading to better hiring decisions and overall recruitment efficiency.